Preclinical Animal Modeling in Medicine 2022
DOI: 10.5772/intechopen.97145
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Glaucoma: Bidirectional Translation between Humans and Pre-Clinical Animal Models

Abstract: Glaucoma is a multifactorial, polygenetic disease with a shared outcome of loss of retinal ganglion cells and their axons, which ultimately results in blindness. The most common risk factor of this disease is elevated intraocular pressure (IOP), although many glaucoma patients have IOPs within the normal physiological range. Throughout disease progression, glial cells in the optic nerve head respond to glaucomatous changes, resulting in glial scar formation as a reaction to injury. This chapter overviews glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…In another example, inspired by the relationship between aging and glaucoma in clinical settings, Lu et al designed retinal tissue reprogramming through the induction of ectopic expression of the four Yamanaka transcription factors and showed reverse age-related vision loss and eye damage in an aging mouse model with glaucoma (6). These and other related studies demonstrated the successful implication of reverse translation in glaucoma research (7)(8)(9).…”
Section: Introduction 1reverse Translation In Glaucoma Studiesmentioning
confidence: 99%
“…In another example, inspired by the relationship between aging and glaucoma in clinical settings, Lu et al designed retinal tissue reprogramming through the induction of ectopic expression of the four Yamanaka transcription factors and showed reverse age-related vision loss and eye damage in an aging mouse model with glaucoma (6). These and other related studies demonstrated the successful implication of reverse translation in glaucoma research (7)(8)(9).…”
Section: Introduction 1reverse Translation In Glaucoma Studiesmentioning
confidence: 99%